Equilibrium policy simulation with random utility models of labor supply - Ugo Colombino (University of Essex, Institute for Social and Economic Research (ISER), 2012)
Many microeconometric models of discrete labor supply include alternative-specific constants meant to account for (possibly besides other factors) the density or accessibility of particular types of jobs (e.g. part-time jobs vs. full-time jobs). The most common use of these models is the simulation of tax-transfer reforms. The simulation is usually interpreted as a comparative static exercise, i.e. the comparison of different equilibria induced by different policy regimes. The simulation procedure, however, typically keeps fixed the estimated alternative-specific constants. In this note we argue that this procedure is not consistent with the comparative statics interpretation. Since the constants reflect the number of jobs and since the number of people willing to work change as a response to the change in tax-transfer regime, it follows that the constants should also change. A structural interpretation of the alternative-specific constants leads to the development of a simulation procedure consistent with the comparative static interpretation. The procedure is illustrated with an empirical example.
Keywords: C35; C53; H31; J22; 330; Random Utility; Discrete Choice; Labor Supply; Policy Simulation; Alternative-Specific Constants; Equilibrium Simulation